THE ROLE OF CAVE NAMES IN THE DEVELOPMENT OF TOURISM IN KAZAKHSTAN - Yeginbayeva, Aigul; Saparov, Kuat; Zhensikbayeva, Nazgul; Nurpeisova, Akerke; Shakhantayeva, Zhanna; Keikin, Yernar; Atis, Evren (Asociatia de Geografie, Turism si Sport, 2024)
Geographical names, including speleonyms, which were once not registered in official sources, have been preserved in the form of missing words or errors in the Russian language. Therefore, the task of their collection and systematization is fixed by many resolutions of the government of the Republic of Kazakhstan and other authorized bodies. One of the issues of determining the ways of implementing the project "sacred geography of Kazakhstan" and the direction of research work is aimed at restoring the names of caves. The purpose of the study is to identify the features of the formation of cave names on the territory of Kazakhstan and the geographical prerequisites for their restoration. Research objectives: to determine the role of physical and geographical conditions of Kazakhstan in the formation of speleonyms; to reflect the patterns and areas of cave distribution in Kazakhstan and to analyze the geographical aspects of the formation of speleonyms; analysis of geographical aspects of the formation of speleonyms; determination of the place of speleonyms as tourist and recreational objects; making proposals for the preservation of caves and Speleonyms of Kazakhstan. The object of the study is caves and other underground parts distributed on the territory of Kazakhstan as special objects of the sacred regions of the country, the subject of the study is the conditions and meaning of the formation of the names of these caves, their geographical prerequisites and opportunities for restoration. The caves will be of great interest from a geomorphological, hydrological, bio-speleological, archaeological and paleozoological point of view. In recent years, they are studied as unique natural landscapes. The importance of caves for speleotourism is also difficult to overestimate.
Keywords: speleotourists; konyr-aulie cave; Geography (General); sightseeing sites; speleotherapy; akmeshit-aulie cave; G; sanctuaries; Geography. Anthropology. Recreation; G1-922; speleotourism; cave ecology; 15. Life on land; 11. Sustainability